Gut-Sourced Vasoactive Intestinal Polypeptide Induced by the Activation of α7 Nicotinic Acetylcholine Receptor Substantially Contributes to the Anti-inflammatory Effect of Sinomenine in Collagen-Induced Arthritis - Yue, MengFan; Zhang, XinYu; Dou, YanNong; Wei, ZhiFeng; Tao, Yu; Xia, YuFeng; Dai, Yue (Frontiers in Pharmacology, 2018)
Sinomenine has long been used for the treatment of rheumatoid arthritis in China. However, its anti-inflammatory mechanism is still debatable because the in vitro minimal effective concentration (≥ 250 μM) is hardly reached in either synovium or serum after oral administration at a therapeutic dose. Recent findings suggest that the α7 nicotinic acetylcholine receptor (α7nAChR) might mediate the inhibitory effect of sinomenine on macrophage activation, which attracts us to explore the anti-arthritis mechanism of sinomenine by taking neuroendocrine-inflammation axis into consideration. Here, we showed that orally administered sinomenine ameliorated the systemic inflammation of collagen-induced arthritis (CIA) rats, which was significantly diminished by either vagotomy or the antagonists of nicotinic acetylcholine receptors (especially the antagonist of α7nAChR), but not by the antagonists of muscarinic receptor. Sinomenine might bind to α7nAChR through interacting with the residues Tyr184 and Tyr191 in the pocket. In addition, the generation of vasoactive intestinal polypeptide (VIP) from the gut of CIA rats and cultured neuron-like cells was selectively enhanced by sinomenine through the activation of α7nAChR-PI3K/Akt/mTOR pathway. The elevated levels of VIP in the serum and small intestine of rats were negatively correlated with the scores of joint destruction. The crucial role of VIP in the anti-arthritic effect of sinomenine was confirmed by using VIP hybrid, a nonspecific antagonist of VIP receptor. Taken together, intestine-sourced VIP mediates the anti-arthritic effect of sinomenine, which is generated by the activation of α7nAChR.